Using NMR, X-ray, and CD analysis in the study on natural products obtained from Vietnamese plant and fungi in terms of pharmaceutical product development - Dinh Thang Tran; Cong Dung Vo; Ngoc Tuan Nguyen; Manh Dung Doan; Yang-Chang Wu; Tian-Shung Wu (Vietnam Journal of Science, Technology and Engineering, 2017)
NMR, X-ray analysis, and CD methods are powerful techniques for the study of absolute configuration of bioactive compounds from natural resources. This study presents the results of a joint-study between Vietnam and Taiwan on the bioactive compounds obtained from Vietnamese plants and fungi. Among the tested compounds, hexatenuin A displayed the most significant inhibition of superoxide anion generation and elastase release. These triterpenoids may be used as potential anti-inflammatory agents.